2004
DOI: 10.1021/ef034027q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acyclic Isoprenoid Hydrocarbons in Wax Derived from Tank Bottom Sludge

Abstract: The oil-soft wax fraction of the microcrystalline wax, extracted from the Bombay High crude tank bottom sludge (Indian origin), has been characterized using gas liquid chromatography (GLC), 1H and 13C nuclear magnetic resonance (NMR), and gas liquid chromatography−mass spectroscopy (GLC−MS). A series of saturated acyclic isoprenoid hydrocarbons have been identified in this wax. These structures have been confirmed by recording GLC-MS spectra of the oil-soft wax fraction at reduced ionization potentials of 30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The abundant mass peaks of LS mass spectra, shown in Figure , also indicate the presence of compounds with molecular formulas of C 40 H 80–2 n ( n = 3–8). This series of compounds with 40 carbons are likely isoprenoid alkanes. Generally, isoprenoid alkanes have relatively more tertiary C–H bonds with relatively high RICO reactivity, resulting in a higher MS peak intensity for the unreduced products. After LiAlH 4 reduction, ketones derived from other saturate compounds (generally with or without fewer tertiary C–H bonds) converted to alcohols, resulting in the decrease in relative abundance of MS peaks, because the “isoprenoid alkane” peaks are also abundant in the product after reduction by LiAlH 4 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The abundant mass peaks of LS mass spectra, shown in Figure , also indicate the presence of compounds with molecular formulas of C 40 H 80–2 n ( n = 3–8). This series of compounds with 40 carbons are likely isoprenoid alkanes. Generally, isoprenoid alkanes have relatively more tertiary C–H bonds with relatively high RICO reactivity, resulting in a higher MS peak intensity for the unreduced products. After LiAlH 4 reduction, ketones derived from other saturate compounds (generally with or without fewer tertiary C–H bonds) converted to alcohols, resulting in the decrease in relative abundance of MS peaks, because the “isoprenoid alkane” peaks are also abundant in the product after reduction by LiAlH 4 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The alkanes with such carbon numbers and variation of carbon numbers correspond to a special class of saturated hydrocarbons: isoprenes. Isoprene alkanes with low carbon numbers (<C 50 ) are important biomarkers in petroleum; however, the high carbon number isoprene alkanes (50, 55, 60, 65, 70) have not been reported. The unusual peak intensity of this series of alcohols with carbon numbers of 50, 55, 60, 65, and 70 is attributed to relative high content of isoprenoid alkanes.…”
Section: Resultsmentioning
confidence: 99%
“…Figure is a mass spectrum that summarizes the data between n -C 34 and n -C 35 of Figure . Ions at m / z 57, 71, 85, and 99, etc., are typical for alkanes . There are also ions coming from alkyl cycloalkanes ( m / z = 97, 111, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…The term wax generally refers to all waxlike solids and liquids found in nature and to those individual organic substances that crystallize on cooling and melt on heating . It has been demonstrated that, in crude oils, waxes may be paraffin type or microcrystalline type, depending on source of the crude oil. Unlike paraffin waxes that consist primarily of n -alkanes, microcrystalline waxes are dominated by cycloalkanes and isoalkanes. Waxes from crude oils may also contain small amounts of aromatic carbon, as well as oxygen, present as acid or ketone …”
Section: Introductionmentioning
confidence: 99%